Microenvironmental Factors and Extracellular Matrix Degradation in Pancreatic Cancer - Binker, Marcelo G; Binker-Cosen, Makena J; Binker-Cosen, Andres A; Cosen-Binker, Laura I (JOP. Journal of the Pancreas, 2014)
Pancreatic cancer is a devastating malady with proclivity for early metastasis, accounting for its poor prognosis. Pancreatic ductal adenocarcinoma, the most common type of pancreatic malignancy, exhibits an over-expression of several growth factors such as epidermal growth factor and transforming growth factor beta, which correlate with a decrease in patient survival. These growth factors as well as hypoxia-reoxygenation conditions have been shown to increase pancreatic tumor cell invasiveness. This review will focus on the signaling pathways used by these distinct microenvironmental factors to promote extracellular matrix degradation and invasion by pancreatic tumor cells. Image: Model for Rac1/ROS/NF-κB-mediated pancreatic cancer invasion.